(untitled) (AWKA JOURNAL OF ENGLISH LANGUAGE AND LITERARY STUDIES, 2023)
This paper analyzes modality system in media reportage of 2018-2020 ASUU strike to canvass for the honouring of the 2009 ASUU-Federal government agreement on the running of public universities. Using Halliday’s systemic functional approach to critical discourse analysis, the use of temporal and modal operators that carry high-, median- and low-value expressions of modalization and modulation by the media in reporting ASUU strike were critically analyzed. These modals were tested on how the newspaper and government agencies oscillate from explicitly objective/subjective modals to implicitly objective/subjective ones depending on the use that give them advantage in the issue under dispute. Data for the study were collected from Daily Sun and This Day newspapers reports of ASUU strike between 208 and 2020. Findings suggest that the media make modality expressions of probability that make them appear objective and at the same time detach themselves from the news reports. Direct reports of the speeches made by the federal government representatives contain modality expressions of obligation and inclination. This shows the exercise of unequal power relationship between the Federal Government of Nigeria and ASUU. This paper therefore concludes that modality choices in media reportage of ASUU strike contribute to prolonged strike actions and recommended that the federal government be sincere in negotiating with ASUU and that news reporters be more objective in their reportage of ASUU strike.